Charged domains in ferroelectric, polycrystalline yttrium manganite thin films resolved with scanning electron microscopy. (13th May 2020) - Rayapati, Venkata Rao; Bürger, Danilo; Du, Nan; Kowol, Cornelia; Blaschke, Daniel; Stöcker, Hartmut; Matthes, Patrick; Patra, Rajkumar; Skorupa, Ilona; Schulz, Stefan E; Schmidt, Heidemarie
Abstract: We have investigated ferroelectric charged domains in polycrystalline hexagonal yttrium manganite thin films (Y1 Mn1 O3, Y0.95 Mn1.05 O3, Y1 Mn0.99 Ti0.01 O3, and Y0.94 Mn1.05 Ti0.01 O3 ) by scanning electron microscopy (SEM) in secondary electron emission mode with a small acceleration voltage. Using SEM at an acceleration voltage of 1.0 kV otherwise homogenous surface charging effects are reduced, polarization charges can be observed and polarization directions (±Pz ) of the ferroelectric domains in the polycrystalline thin films can be identified. Thin films of different chemical composition have been deposited by pulsed laser deposition on Pt/SiO2 /Si structures under otherwise same growth conditions. Using SEM it has been shown that different charged domain density networks are existing in polycrystalline yttrium manganite thin films.